LEGAL REVIEW OF CORPORATE CRIMINAL LIABILITY IN CORRUPTION CRIMINAL ACTS - Tri Sandi; Lidya Ramadhani Hasibuan; Aulia Rahman Hakim Hasibuan (PT. Sinergi Legal Publisher, 2025)
The phenomenon of corruption involving corporations is increasingly rampant in Indonesia. As a legal entity, a corporation can be held criminally responsible for corruption offenses committed. This research aims to analyze the legal provisions regarding corporate criminal liability in corruption crimes and the forms of criminal responsibility that can be imposed on corporations. The research method used is normative legal research with an approach based on laws and regulations, as well as case study analysis of Supreme Court rulings related to corruption offenses committed by corporations. The research findings indicate that the legal framework concerning corporate criminal liability in corruption offenses is regulated in various laws such as Law No. 31 of 1999 jo. Law No. 20 of 2001 on the Eradication of Corruption Crimes, as well as Supreme Court Regulation No. 13 of 2016 on Procedures for Handling Criminal Cases Involving Corporations. Forms of criminal liability that can be imposed on corporations include fines, corporate dissolution, and revocation of business licenses. The case study of Supreme Court Decision No. 927 K/Pid.Sus-LH/2021 shows that the Supreme Court rejected the cassation request and revised the sentence imposed on the corporation, reducing the fine from IDR 20 billion to IDR 2 billion, with the provision that assets be seized if the fine is not paid.